Participation of children with and without disabilities in recreational and leisure activities: a pilot study - Zulkifly, Mohd Afiq Taqiuddin (Universiti Sains Malaysia, 2014)
Participation in recreational and leisure activity is important for children development. It also promotes social well-being, as well as physical and mental health. learn skills for teamwork, self-discipline, sportsmanship, leadership, and socialization. All children would benefit from recreational and leisure activities including children with disabilities. This study investigated level of activity participation of children with and without disability in recreational and leisure activities and how those spent their leisure time. Forty children aged between 5 and 12 years old were recruited in this study and divided equally into two groups, namely Typical Development children (TD) and children with Intellectual Disability (ID). The Modified Activities Questionnaire (MAQ) was used to measure children participation in recreational and leisure activities. The top five most frequent recreational activities participated by TD children were cycling, running, football, walking and badminton. Conversely, the top five most frequent recreational activities participated by ID children were walking, dancing, running, singing and playing football. It was found that TD children have higher level of activity participation in recreational activities than ID children. In term of leisure activities, the top five most frequent participated by TD children were watching TV, playing computer games, listening to music, playing video games and leisure reading (book/comic). The top five most frequent leisure activities participated by ID children were watching TV. painting, water activities, listening to music, leisure reading (book/comic) and playing video games. This study found that the Recreational and leisure activities provide learning opportunities for children such as level of participation in leisure activities of TD and ID children were similar. It was also found that TD children tend to participate more in active leisure but ID children participated more in passive leisure.